Ant Abundance, identification and relation with cocoa pest attacks under several shade trees. - Abied Khafidhan; Rahayu Widyastuti; Soetanto Abdoellah (Indonesian Coffee and Cocoa Research Institute, 2021)
Ants are soil macrofauna that plays an essential role in preventing pods of cocoa (Theobroma cacao L.) from Helopeltis antonii and Conopomorpha cramerella attack. However, the method of those pests control primarily using pesticides and that will disturbed ant's life. This research aims to determine the abundance and diversity of ants in cocoa plantations with different shade and to determine the correlation between ant abundance and intensity of pest attack from Helopeltis antonii and Conopomorpha cramerella. Ants sample was carried out using pitfall traps and Berlese funnels based on purposive sampling method. The results showed that five subfamilies were found in cocoa plantations with different shade. Subfamily Myrmicinae was the dominant group in all observation sites. The ant abundance has a strong correlation with intensity of pest attack. This was influenced by a role of the ant as natural enemies from Helopeltis antonii and Conopomorpha cramerella.